Perceptions of occupational and physiotherapists regarding their communication with clients with post-stroke aphasia during rehabilitation - Tonsing, Kerstin Monika (University of Pretoria, 2024)
Mini Dissertation (MAugmentative and Alternative Communication)--University of Pretoria, 2023.